Real-Time Tracking of Diagnostic Discrepancies in Electronic Health Records for Improved Predictive Modeling - Elizabeth A. Trader; Varadraj P. Gurupur (IEEE Access)
Diagnostic discrepancies, a persistent threat in healthcare, compromise patient outcomes and hinder effective treatment. Despite their prevalence, addressing diagnostic discrepancies remains a complex challenge due to the limitations of traditional methods and fragmented and inaccessible data. The emergence of machine learning (ML) offers a promising solution by analyzing vast medical datasets to detect subtle disease signatures and improve treatment personalization with unparalleled precision. However, data quality and availability remain significant barriers, as incompleteness, inconsistencies, and biases can distort ML models, leading to potentially harmful misinterpretations. This paper highlights the critical role of diagnostic discrepancy statistics in overcoming these challenges and proposes a standardized data schema that ensures interoperable, real-time, and historical data without compromising patient privacy. By addressing the current lack of accessible diagnostic discrepancy data, the schema lays a foundation for more effective analysis, better patient outcomes, and improved use of machine learning in healthcare. The key contribution of this paper is the framework that allows for increased data transparency and improved data quality.